2017
DOI: 10.1038/srep46499
|View full text |Cite
|
Sign up to set email alerts
|

Host Determinants of Expression of the Helicobacter pylori BabA Adhesin

Abstract: Expression of the Helicobacter pylori blood group antigen binding adhesin A (BabA) is more common in strains isolated from patients with peptic ulcer disease or gastric cancer, rather than asymptomatic colonization. Here we used mouse models to examine host determinants that affect H. pylori BabA expression. BabA expression was lost by phase variation as frequently in WT mice as in RAG2−/− mice that do not have functional B or T cells, and in MyD88−/−, TLR2−/− and TLR4−/− mice that are defective in toll like r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 74 publications
0
17
0
1
Order By: Relevance
“…However, neither immunoproteomic studies (38,39) nor serologic responses in macaques (23) have identified BabA or BabB as an immunodominant antigen and its expression appears to have no effect on gastritis. Furthermore, BabA expression is lost in recombination-activating gene-deficient mice that do not express functional B or T cells (46). Therefore, while the basis for selection against BabA expression is unknown, it is not likely classical immune evasion and it does not require the capacity to attach to Leb.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither immunoproteomic studies (38,39) nor serologic responses in macaques (23) have identified BabA or BabB as an immunodominant antigen and its expression appears to have no effect on gastritis. Furthermore, BabA expression is lost in recombination-activating gene-deficient mice that do not express functional B or T cells (46). Therefore, while the basis for selection against BabA expression is unknown, it is not likely classical immune evasion and it does not require the capacity to attach to Leb.…”
Section: Discussionmentioning
confidence: 99%
“…showed an independent selective pressure for loss of BabA expression and overexpression of BabB. In addition, loss of BabA expression was reported to be independent of adaptive immunity or Toll‐like receptor signaling …”
Section: Helicobacter Pylori Gastric Colonization and Acid Resistancementioning
confidence: 99%
“…Observed mechanisms of negative selection of bab A included phase variation by slipped stranded mispairing and gene conversion with bab B, which may directly confer a fitness advantage . In addition, the negative selection of bab A was observed even in the absence of host TLR signaling …”
Section: Virulence Factorsmentioning
confidence: 99%
“…BabA is known to be important in the initial colonization of H. pylori, but was negatively selected after a few days' and up to 20 weeks' infection in both mice and rhesus macaques. 32,33 Observed mechanisms of negative selection of babA included phase variation by slipped stranded mispairing and gene conversion with babB, which may directly confer a fitness advantage. 33 In addition, the negative selection of babA was observed even in the absence of host TLR signaling.…”
Section: Outer-membrane Protein(s)mentioning
confidence: 99%
See 1 more Smart Citation